Avaliação do ângulo nasolabial, em radiografias cefalométricas laterais, dividido em ângulo superior e inferior, por uma linha paralela ao plano de frankfort, em índividuos portadores de má-oclusão classe II e classe III de angle - Salgado, José Antonio Pereira [UNESP] (2002)
This study consisted of the analysis nasolabial angle and its division in superior and inferior angle, by a parallel line to the Frankfort Plane, pass on the point Subnasal. 120 cephalometric x-rays lateral norm were used, from patients bearers of Class II and Class llI of Angle occlusion, with 60 patient each group, 30 female and 30 male, age group from 13 to 43 years, with age average of 241,03+77,78 months. The results obtained were to the nasolabial angle the general average of 106,42'+9,87º being for the Class II the average of 109,37+9,10 and for the Class III of 103,48+9, 79, for male average of 107,02+ 10,32 and for female of 105,83+9,44. The superior angle presented average of 22,092°+8,831º, for Class II the average of 26,48+8,68 and for Class lIl of 17,708+6,543,for male average of 22,40+8,85 and for female of 21,78+8,87. For inferior angle avarage of 84,429º+8,717, for Class II average of 82,93+7,99 and for Class lIl average of 85,93+9,21, for male of 84,63+9,21 and for female of 84,23+8,26. It was concluded for nasolabial angle and for superior angle, the individuals Class II differ from individuals Class III (Class III larger than Class lII), with statistically significant difference; for nasolabial angle and for superior angle without estatistically significant difference for sex and interaction among sex with occlusion; for the inferior angle without estatistically signiflcant difference the data for occlusion, sex and their interactions